2003
DOI: 10.1159/000068780
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Intrathecal Sulfatide and TNF-α Levels in Patients with Vascular Dementia

Abstract: Objectives: Subcortical vascular dementia (SVD) is associated with white matter lesions and demyelination. The aim of the present study was to examine the cerebrospinal fluid (CSF) levels of TNF-α, a proinflammatory cytokine mediating myelin damage, in SVD patients. The intrathecal TNF-α levels were related to the clinical symptoms of dementia, as well as to intrathecal levels of sulfatide, a marker of white matter degradation, and of neurofilament, a marker of neuronal degeneration. Methods: CSF levels of TNF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Whether gradual accumulation of sulfatides in neuronal cells is associated with the pathogenesis of PD remains to be elucidated. Very recently, Tarkowski and colleagues [79] demonstrated alterations in sulfatide mass in CSF of subjects with vascular dementia, suggesting that apoE-mediated sulfatide metabolism might be involved in this disease too. Although available evidence supports the conclusion that sulfatides are only synthesized in oligodendrocytes [64,65], the presence of sulfatides in neurons and astrocytes (e.g.…”
Section: Modulation Of Sulfatide Metabolism By Apoementioning
confidence: 99%
“…Whether gradual accumulation of sulfatides in neuronal cells is associated with the pathogenesis of PD remains to be elucidated. Very recently, Tarkowski and colleagues [79] demonstrated alterations in sulfatide mass in CSF of subjects with vascular dementia, suggesting that apoE-mediated sulfatide metabolism might be involved in this disease too. Although available evidence supports the conclusion that sulfatides are only synthesized in oligodendrocytes [64,65], the presence of sulfatides in neurons and astrocytes (e.g.…”
Section: Modulation Of Sulfatide Metabolism By Apoementioning
confidence: 99%
“…Inflammatory cytokines are elevated during acute stroke 1,2 and in the CSF of individuals with subcortical vascular dementia. 3 Furthermore, inflammation is a well-documented feature 4 and purported risk factor 5 for AD. Amyloid deposition stimulates neuroinflammatory processes with neurotoxic effects that exacerbate the pathogenesis of AD and increase neuronal damage.…”
mentioning
confidence: 99%
“…Fredman et al [15] found significantly elevated CSF sulfatide levels in patients with vascular dementia (n = 20) compared to patients with AD (n = 43) and controls (n = 20). Tarkowski et al [18] studied CSF sulfatide and TNF-α in patients with SVD (n = 17) and healthy controls (n = 26) and found positive correlations in patients with SVD, suggesting that the apoptosis-inducing cytokine leads to the death of oligodendrocytes, thereby contributing to white matter degeneration. Tullberg et al [16] studied WML in patients with normal pressure hydrocephalus (NPH, n = 43) and subcortical arteriosclerotic encephalopathy (SAE, n = 19), respectively, and found that CSF sulfatide levels distinguish between NPH and SAE.…”
Section: Discussionmentioning
confidence: 99%
“…An elevated CSF/serum albumin ratio has been demonstrated in patients with SVD and WML as a sign of an impaired integrity of the BBB [14]. Sulfatide, a glycosphingolipid enriched in myelin, elevated in CSF in patients with WML, has been regarded as a marker of demyelination [15][16][17][18]. Neurofilament protein light subunit (NFL), a cytoskeletal protein in large myelinated axons, has been found to be significantly increased in patients with SVD [19] and in relation to WML in other clinical forms of dementia [20].…”
Section: Neurochemical Markersmentioning
confidence: 99%